Detection and characterization of local inverted repeats regularities - Bastos, Carlos A. C. (2021)
To explore the inverted repeats regularities along the genome sequences, we propose a sliding window method to extract the concentration scores of inverted repeats periodic regularities and the total mass of possible inverted repeats pairs. We apply the method to the human genome and locate the regions with the potential for the formation of large number of hairpin/cruciform structures. The number of found windows with periodic regularities is small and the patterns of occurrence are chromosome specific.